2013
DOI: 10.1016/j.seizure.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Severity of depressive symptomatology and functional impairment in children and adolescents with temporal lobe epilepsy

Abstract: Children with TLE had moderate to severe DS early in the course of their disease with a relevant impact on their global functional activities, especially considering adolescents. Epilepsy severity seems not to be correlated to the severity of DS, contradicting the idea of a cause-consequence relationship. More systematic research is needed to better understand the association of depressive disorders in children and adolescents with TLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…The association of depression or anxiety with specific seizure types or localization is less well established. However, two small studies suggest that depression is more often present in children with temporal lobe seizure localization (67,68). This finding is consistent with literature associating depressive phenomena with temporal lobe pathology in persons without epilepsy (69).…”
Section: Mood Disorder and Anxietysupporting
confidence: 87%
“…The association of depression or anxiety with specific seizure types or localization is less well established. However, two small studies suggest that depression is more often present in children with temporal lobe seizure localization (67,68). This finding is consistent with literature associating depressive phenomena with temporal lobe pathology in persons without epilepsy (69).…”
Section: Mood Disorder and Anxietysupporting
confidence: 87%
“…31 Although the type, localization, and onset age of seizures do not appear to be a risk factor for anxiety and depression, 11,15,42 two studies show that depression is common in children with epilepsy with temporal lobe localization. 43,44 This finding is also compatible with the medical literature that associates depressive phenomenon with temporal lobe pathologies. 45,46 Additional low intelligence scores and uncontrolled resistant seizures are also factors that increase the risk of anxiety disorder and depression.…”
Section: Factors About Child Characteristicssupporting
confidence: 91%
“…However, in 2013, the study by Pereira et al [24] suggested that the severity of depression was not associated with epilepsy control, duration and onset age in children with epilepsy.…”
mentioning
confidence: 98%